Yellow fever and pregnancy - Maguiña Vargas, Ciro (2015)
Yellow fever in Peru is currently wild. The infection is localized in some endemic focal points in the Peruvian jungle. Lethality is high and may be close to 50%. There is no antiviral therapy and prevention is effective by vaccination. When pregnant women are infected by the yellow fever virus they can present various complications, fetal and maternal, including death of both fetus and mother. Vaccination against yellow fever is with live virus and is contraindicated during pregnancy.